'This is what a radical intervention could look like': an interview with Barbara Ransby. (October 2020) - Bourne, Jenny
An interview with Chicago-based Black historian, activist and writer Barbara Ransby in July 2020 as to how to understand the significance of the Movement for Black Lives (M4BL) uprisings across the US. Ransby defines the movement and the forces that made George Floyd's murder a pivotal point for so many people, bringing them on to the streets in over 500 locations. She explains the gestation of the movement against 'racial capitalism' from 2012 onwards and its current political formation as made up of an array of forces. The largest most organised coalition is the Movement for Black Lives (M4BL). She traces the white Left's unwillingness to see the Black working class as now the defining point of class politics and addresses issues of police violence, incarceration and white supremacy. Organic solidarity is developing between progressive groups around an abolition agenda, which is simultaneously about dismantling the carceral state and building new institutions.